Using combined optimization and vacuum freeze drying technology to prepare directed vat set starter for "Niuganba, " a fermented beef. Issue 9 (25th June 2021) - Tian, Xueyi; Liu, Hanyu; Wang, Xiao; Li, Cuiqin; He, Laping; Zeng, Xuefeng
Abstract: Niuganba (NGB), fermented beef meat, is a traditional delicacy of China. Directed vat set starters can regulate the quality and shorten the fermentation time of NGB. In this study, the Box‐Behnken experiment and a single factor test were used to prepare a directed vat set starter containing Lactobacillus pentosus MT‐4, Staphylococcus xylosus, and fragrant yeast for fermentation. The concentration of trehalose, mannitol, and sodium glutamate in the most effective formulation of the protective agent were 9.27%, 6.57%, and 4.73% for freeze‐dried fragrant yeast, 10.66%, 6.19%, and 5.77% for the freeze‐dried S . xylosus, and 10.02%, 6.19%, and 4.76% for the freeze‐dried L . pentosus MT‐4, respectively. Under the optimal freeze‐drying conditions, the highest survival rates of fragrant yeast, S . xylosus, and L . pentosus MT‐4 after freeze‐drying were 89.76%, 84.46%, and 89.4%, respectively. NGB fermented using directed vat set starters required less fermentation time and had enriched flavor than traditionally fermented beef. Practical applications: Niuganba (NGB) in China is produced mostly via traditional methods. Primary producers of NGB are small‐ and medium‐sized enterprises that prepare NGB via the traditional manual method. Traditional methods of NGB production have certain disadvantages compared to large‐scale and automated methods. Directed vat set starters can significantly optimize traditional processing and technology for NGB production; besides, it can extend the shelf life of NGB. Thus, directed vat set starters for NGB have significant implications on the NGB's large‐scale and automated commercial production.